Incidence and Management of Scabies in Boarding School: Perception from Residents - Siti Aminah Tri Susila Estri; Muhammad Khotibudin (IJNP (Indonesian Journal of Nursing Practices), 2022)
Background: Scabies is a Sarcoptes scabei infection of the human epidermis. This disease is often found in patients who live in groups, such as in boarding schools. Although the risk factors, knowledge, and treatment of scabies have been known, the incidence of scabies in Islamic boarding schools is still high. There is a perception that scabies is a common disease among students. Scabies can interfere with the quality of life or activities of sufferers.Objective: Therefore, it is necessary to study the perceptions of managers and residents of boarding schools regarding the management and incidence of scabies in Islamic boarding schools.Methods:  This research was conducted in an Islamic boarding school using a qualitative method. The information was obtained from 40 participants: school leaders or managers, teachers, non-educational staff, students, and parents of students in boarding schools.  Information was collected using a google form, then coded and grouped based on the item. This study has been declared ethically feasible by the research ethics committee.Result: The result showed that participants considered scabies a skin disease that could interfere with daily activities. It could be transmitted through direct contact, using toiletries or clothes together.  School leadership policies, based on good knowledge, followed by the appropriate behavior of all school residents, had an important role in the incidence of scabies in boarding schools.Conclusion: The participants had explained similar perceptions about scabies and their management in their boarding school. Participants agreed that scabies could be eliminated by jointly implementing healthy lifestyle behaviors based on Islamic values. The researchers suggest continuing and improving activities and management of students with scabies so that the school can be free from scabies. Second, further research can be carried out in schools with a high incidence of scabies so that it can be compared and find the basic problem about why there is still a high incidence of scabies in boarding schools in Indonesia.